(untitled) (Research, Society and Development, 2020)
Tithonia diversifolia (Hemsl) A. Gray, commonly known as “Mexican Sunflower”, is a perennial herbaceous plant of the Asteraceae family, native to Mexico and Central America. At present, however, this species is widely found in many countries outside of these areas, including Brazil. It has been the subject of many scientific studies which by highlighting the chemical constitution of its main structures such as leaves, inflorescences, stalk and roots, consequently bring to light this species’ nutritional and therapeutic potential in current literature. The aim of this study is to produce a literature review on the ethnobotanical aspects and possible pharmacological applications of T. diversifolia, with emphasis on its chemical composition, morphological characteristics and pharmacotherapeutic applications. The present study is a bibliographical, exploratory and qualitative research, carried out due to the need to elucidate the proposed theme and fulfills the role of reviewing the specific bibliography on the addressed topic. Based on the produced bibliography, it is noticeable that Tithonia diversifolia (Hemsl) A. Gray is a plant of potential nutritional and pharmacological interest. In general, the studies reviewed here strengthen and highlight the evidence of the diverse applications of this species by traditional medicine, which, in turn, contribute to the development of studies that guarantee the identification of active constituents and their respective biotechnological applications.